Mengukur Tingkat Kematangan Learning Management System (LMS) Menggunakan Framework COBIT 5 Domain MEA dan EDM (Studi Kasus: Universitas Hindu Indonesia) - Trisnawati, Ni Komang Adi; Jaya, I Kadek Noppi Adi; Dewi, Ida Ayu Utari (RESI : Jurnal Riset Sistem Informasi, 2025)
LMS is a platform for managing, delivering and tracking online training or education. COBIT is a framework that will be used for information technology (IT) management and governance. The MEA Domain ensures the system has the appropriate design and controls required to comply with regulatory requirements. Meanwhile, EDM will ensure goals are achieved by evaluating stakeholder needs, conditions and choices. The data collection process used is Interview, Observation, Questionnaire. The process carried out to determine information system technology that is in accordance with the COBIT 5 standard is Maturity Level analysis and Gap Analysis. The Maturity Level of the Learning Management System at Hindu Indonesia University using COBIT 5 MEA and EDM Domains with the COBIT 5 framework reaches Level 4: Predictable Process. The level of gap in the Learning Management System at Indonesian Hindu University is 0.52 in MEA01 and 0.5 in EDM01. To reach Maturity Level 5, managers need to improve the quality of governance, supervision and stakeholder involvement in the LMS management process.